Red mud-based cementitious material and method for preparing the same
Patent Information
- Application Number
- CN202611500303.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-24
- Publication Date
- 2026-10-30
AI Technical Summary
赤泥预脱钠工艺复杂、成本高,难以规模化应用;仅简单掺加矿物掺合料,只能在水化阶段对游离钠进行有限吸附,无法在熟料烧制阶段对钠进行矿物固封;表面涂层防护属于被动防护,涂层破损之后泛碱问题会再次发生
1、本发明通过改性赤泥和辅助改性剂的协同作用以及熟料煅烧过程中的矿物调控作用,使硫铝酸钙等活性矿物晶格固溶赤泥中带入的部分钠离子,从熟料矿物层面减少可溶性钠盐生成,降低钠离子向外浸出迁移率和迁移速率。改性赤泥和辅助改性剂的协同作用形成二次固钠、水化产物致密阻渗,实现对赤泥基胶凝材料泛碱行为的有效抑制。
Smart Images

Figure CN123003166A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of cementitious materials technology, specifically to a red mud-based cementitious material and its preparation method. Background Technology
[0002] For a long time, cement production has been plagued by high energy consumption and high pollution, accounting for approximately 15% of the nation's total carbon emissions. Utilizing bulk industrial solid waste to prepare cementitious materials is an important way for the building materials industry to reduce carbon emissions. Red mud is a highly alkaline industrial solid waste generated during alumina smelting, and its massive stockpiles pose a risk of alkali leakage and groundwater contamination if stored directly. Using red mud to prepare high-ferric sulfoaluminate cementitious materials can achieve the resource utilization of red mud. Furthermore, the calcination temperature of high-ferric sulfoaluminate clinker is lower than that of ordinary silicate cement, giving it a low-carbon advantage.
[0003] Bayer process red mud contains a large amount of sodium. When it is used as a raw material to produce ferroaluminate clinker, part of the sodium component is dissolved in the clinker minerals, while the other part is converted into soluble sodium salt phases such as sodium sulfate. When the cementitious material comes into contact with water, the soluble sodium salts dissociate and release sodium ions, which migrate to the surface of the product with the pore solution. After the water evaporates, the sodium salts precipitate, causing efflorescence and salting-out, resulting in whitening, powdering, and peeling of the component surface. This seriously affects the appearance and durability of the product and restricts the engineering promotion of red mud-based ferroaluminate clinker.
[0004] Current technologies for suppressing efflorescence in cement-based materials mainly include: pre-sodium removal treatment of red mud, subsequent external addition of mineral admixtures, and application of protective coatings to the component surface. The pre-sodium removal process of red mud is complex and costly, making large-scale application difficult. Simply adding mineral admixtures can only achieve limited adsorption of free sodium during the hydration stage, failing to mineral-encapsulate sodium during the clinker firing stage. Surface coating protection is a passive measure; efflorescence will recur once the coating is damaged. Currently, there is a lack of a comprehensive preparation process for red mud-based high-ferrous sulfoaluminate cementitious materials that integrates raw material formulation, clinker firing, and auxiliary cementitious material compounding to achieve multi-stage synergistic suppression of efflorescence. Summary of the Invention
[0005] To address the shortcomings of existing technologies, the present invention aims to provide a red mud-based cementitious material and its preparation method. The invention includes raw material formulation and clinker calcination. By precisely controlling the raw material ratio, sodium ions are increased to dissolve in the calcium sulfoferrite aluminate mineral lattice. In the compounding stage, desulfurized gypsum, fly ash, and auxiliary modifiers are added. The sodium sulfate alkali inside the clinker activates the fly ash to achieve secondary sodium ion fixation. Combined with the dense matrix structure after hydration, sodium ion leaching is slowed down. Multiple mechanisms synergistically inhibit efflorescence, solving the problem of efflorescence in the preparation of cementitious materials from high-sodium red mud. In summary, the present invention fixes sodium ions from two aspects: clinker calcination and the addition of auxiliary cementitious materials, reducing the leaching of free sodium ions, thus obtaining a red mud-based cementitious material that inhibits efflorescence.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing a red mud-based cementitious material includes the following preparation steps: S1. By weight, 15-25 parts modified red mud, 30-50 parts desulfurized gypsum, 20-40 parts aluminum ash, 10-15 parts coal gangue, and 0.5-1.5 parts borax are mixed evenly and calcined in a high-temperature furnace to obtain red mud-based high-iron sulfoaluminate cementitious material clinker. S2. Add 10-20 parts of desulfurized gypsum, 25-35 parts of Class II fly ash, and 10-15 parts of auxiliary modifier to the red mud-based high-iron sulfoaluminate cementitious material clinker obtained in step S1, mix evenly and grind through a 200-mesh sieve to obtain the red mud-based cementitious material. The preparation of modified red mud includes the following steps: S11. By weight, mix and stir 80-100 parts of red mud (Bayer process high-sodium red mud), 6-10 parts of potassium hydroxide, 0.5-2.5 parts of calcium chloride, 0.5-1.5 parts of magnesium sulfate, 2-3 parts of desulfurized gypsum, and 10-16 parts of carbide slag for 20-30 minutes. S12. Add 40-60 parts of deionized water to the mixture obtained in step S11, stir into a paste, age at room temperature for 12-24 hours, dry in an oven at 100-110℃, place in a high-temperature furnace, heat to 750-850℃, keep warm for 30-60 minutes, and cool to room temperature. S13. Mix the product obtained in step S12 with 250-300 parts of surface modifier, stir and react in a water bath at 60-80℃ for 12-24 hours, filter and wash 3-4 times, dry at 58-60℃ to constant weight and pass through a 200-mesh sieve to finally obtain modified red mud.
[0007] Preferably, the preparation of the surface modifier includes the following steps: S131. By mass, mix 1-2 parts KH-550, 0.5-1 parts titanate coupling agent NDZ-101, 15-20 parts anhydrous ethanol and 1-3 parts deionized water, adjust the pH to 4-5 with glacial acetic acid, and hydrolyze with magnetic stirring for 30-60 minutes. S132. Mix 25-30 parts of stearic acid, 0.4-1 parts of hexadecyltrimethylammonium bromide and 500-700 parts of anhydrous ethanol, and stir at 200-400 r / min in a water bath at 60-80℃ until completely dissolved. S133. Mix the solutions obtained in steps S131 and S132 and stir at a speed of 200-300 r / min for 10-20 min to finally obtain the surface modifier.
[0008] Preferably, the preparation of the auxiliary modifier includes the following steps: S21. By weight, 10-15 parts of glass powder and 10-15 parts of slag powder are dry ball-milled in a ball mill at a speed of 200-300 r / min for 15-30 min, and then passed through a 200-mesh sieve to obtain primary mixed powder. S22. Stir 0.5-1 parts of polycarboxylate superplasticizer and 0.2-0.5 parts of naphthalene-based high-efficiency superplasticizer at low speed until they are evenly mixed to obtain a secondary mixed powder; S23. Mix the primary mixed powder, the secondary mixed powder, and 0.3-1 part of organosilicon water-repellent agent in a V-type mixer at 20-40 r / min for 10-20 min to finally obtain the auxiliary modifier.
[0009] Preferably, the heating rate of calcination in step S1 is 5-10℃ / min.
[0010] Preferably, the calcination temperature in step S1 is 1100-1200℃, and the calcination holding time is 10-30min.
[0011] Preferably, the stirring speed in step S11 is 30-50 r / min.
[0012] Preferably, the heating rate of the high-temperature furnace in step S12 is 5-10℃ / min.
[0013] Preferably, the cleaning solution used in step S13 is anhydrous ethanol.
[0014] Preferably, the stirring speed in step S131 is 200-300 r / min.
[0015] A red mud-based cementitious material is prepared by the above-described preparation method.
[0016] Compared with the prior art, the beneficial effects of the present invention are: 1. This invention utilizes the synergistic effect of modified red mud and auxiliary modifiers, along with mineral regulation during clinker calcination, to dissolve some sodium ions introduced into the red mud into the lattice of active minerals such as calcium sulfoaluminate. This reduces the formation of soluble sodium salts at the clinker mineral level, thereby lowering the leaching migration rate and extent of sodium ions. The synergistic effect of modified red mud and auxiliary modifiers forms secondary sodium fixation and dense, impermeable hydration products, effectively suppressing the efflorescence behavior of red mud-based cementitious materials.
[0017] 2. This invention constructs a multi-component synergistic "chemical bonding-physical covering" dual-effect hydrophobic layer through surface modifiers, realizing a fundamental transformation of the surface of red mud particles from hydrophilic to superhydrophobic, cutting off the "water-salt" migration chain necessary for efflorescence from the source, and endowing red mud-based cementitious materials with active anti-efflorescence ability.
[0018] 3. This invention relates to the field of red mud resource utilization and efflorescence inhibitory cementitious materials. It is low in cost, simple in process and equipment, and easy to scale up industrial production. While disposing of large quantities of red mud solid waste, it solves the engineering pain points of easy efflorescence and whitening and salt precipitation and powdering of cementitious material products made from high sodium red mud, and has good market value. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation process of the red mud-based cementitious material of the present invention. Figure 2 This is a flow chart of the preparation process of the modified red mud of the present invention; Figure 3 This is a flow chart of the preparation process of the auxiliary modifier of the present invention; Figure 4 This is a flow chart of the preparation process of the surface modifier of the present invention; Figure 5 Image of the red mud-based high-ferric sulfoaluminate cementitious material clinker obtained in Example 1 of this invention; Figure 6 The image shows the XRD pattern of the red mud-based high-ferric sulfoaluminate cementitious material clinker obtained in Example 1 of this invention. Figure 7 This is a finished product image of the red mud-based cementitious material obtained in Example 1 of the present invention. Detailed Implementation
[0020] The present invention will now be clearly and completely described in conjunction with embodiments thereof. Obviously, the described embodiments are merely some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0021] Please see Figures 1-7 The present invention provides a technical solution: Example 1 A method for preparing a red mud-based cementitious material: Before preparing red mud-based cementitious materials, surface modifiers, modified red mud, and auxiliary modifiers are prepared first: The preparation of surface modifiers includes the following steps: S131. Mix 1g KH-550, 0.5g titanate coupling agent NDZ-101, 15g anhydrous ethanol and 1g deionized water, adjust the pH to 4 with glacial acetic acid, and hydrolyze with magnetic stirring at 200r / min for 30min. S132. Mix 25g stearic acid, 0.4g hexadecyltrimethylammonium bromide and 500g anhydrous ethanol, and stir at 200r / min in a 60℃ water bath until completely dissolved; S133. Mix the solutions obtained in steps S131 and S132 and stir at 200 r / min for 10 min to finally obtain the surface modifier.
[0022] The preparation of modified red mud includes the following steps: S11. Mix 80g red mud, 6g potassium hydroxide, 0.5g calcium chloride, 0.5g magnesium sulfate, 2g desulfurized gypsum, and 10g carbide slag, and mix at a speed of 30r / min for 20min; S12. Add 40g of deionized water to the mixture obtained in step S11, stir into a paste, age at room temperature for 12h, dry in a 100℃ oven, place in a high-temperature furnace, heat to 750℃ at a heating rate of 5℃ / min, keep warm for 30min, and cool to room temperature. S13. The product obtained in step S12 is mixed with 250g of surface modifier and stirred in a water bath at 60℃ for 12h. After filtration, it is washed three times with anhydrous ethanol and dried at 58℃ to constant weight and passed through a 200-mesh sieve to finally obtain modified red mud.
[0023] The preparation of the auxiliary modifier includes the following steps: S21. Mix 10g of glass powder and 10g of slag powder in a ball mill at a speed of 200r / min for 15min, and then pass the mixture through a 200-mesh sieve to obtain a primary mixed powder. S22. Stir 0.5g of polycarboxylate superplasticizer and 0.2g of naphthalene-based high-efficiency superplasticizer at low speed until they are evenly mixed to obtain a secondary mixed powder; S23. Mix the primary mixed powder, the secondary mixed powder and 0.3g of organosilicon water-repellent agent in a V-type mixer at 20r / min for 10min to finally obtain the auxiliary modifier.
[0024] The preparation of red mud-based cementitious materials includes the following steps: S1. Mix 15g modified red mud, 30g desulfurized gypsum, 20g aluminum ash, 10g coal gangue and 0.5g borax evenly, and calcine in a high-temperature furnace at a heating rate of 5℃ / min, a calcination temperature of 1100℃ and a holding time of 10min to obtain red mud-based high-iron sulfoaluminate cementitious material clinker. S2. Add 10g of desulfurized gypsum, 25g of Class II fly ash, and 10g of auxiliary modifier to the red mud-based high-iron sulfoaluminate cementitious material clinker obtained in step S1, mix evenly, and grind through a 200-mesh sieve to obtain the red mud-based cementitious material.
[0025] Example 2 A method for preparing a red mud-based cementitious material: Before preparing red mud-based cementitious materials, surface modifiers, modified red mud, and auxiliary modifiers are prepared first: The preparation of surface modifiers includes the following steps: S131. Mix 2g KH-550, 1g titanate coupling agent NDZ-101, 20g anhydrous ethanol and 3g deionized water, adjust the pH to 5 with glacial acetic acid, and hydrolyze with magnetic stirring at 300r / min for 60min. S132. Mix 30g stearic acid, 1g hexadecyltrimethylammonium bromide and 700g anhydrous ethanol, and stir at 400r / min in an 80℃ water bath until completely dissolved; S133. Mix the solutions obtained in steps S131 and S132 and stir at 300 r / min for 20 min to finally obtain the surface modifier.
[0026] The preparation of modified red mud includes the following steps: S11. Mix 100g red mud, 10g potassium hydroxide, 2.5g calcium chloride, 1.5g magnesium sulfate, 3g desulfurized gypsum, and 16g carbide slag, and mix at a speed of 50r / min for 30min; S12. Add 60g of deionized water to the mixture obtained in step S11, stir into a paste, age at room temperature for 24h, dry in an oven at 110℃, place in a high-temperature furnace, heat to 850℃ at a heating rate of 10℃ / min, keep at that temperature for 60min, and cool to room temperature. S13. The product obtained in step S12 is mixed with 300g of surface modifier and stirred in a water bath at 80℃ for 24h. After filtration, it is washed four times with anhydrous ethanol and dried at 60℃ to constant weight before passing through a 200-mesh sieve to finally obtain modified red mud.
[0027] The preparation of the auxiliary modifier includes the following steps: S21. Mix 15g of glass powder and 15g of slag powder in a ball mill jar by dry ball milling at 300r / min for 30min, and then pass the mixture through a 200-mesh sieve to obtain a primary mixed powder. S22. Stir 1g of polycarboxylate superplasticizer and 0.5g of naphthalene-based high-efficiency superplasticizer at low speed until they are mixed evenly to obtain a secondary mixed powder; S23. Mix the primary mixed powder, the secondary mixed powder and 1g of organosilicon water-repellent agent in a V-type mixer at 40r / min for 20min to finally obtain the auxiliary modifier.
[0028] The preparation of red mud-based cementitious materials includes the following steps: S1. Mix 25g modified red mud, 50g desulfurized gypsum, 40g aluminum ash, 15g coal gangue and 1.5g borax evenly, and calcine in a high-temperature furnace at a heating rate of 10℃ / min, a calcination temperature of 1200℃ and a holding time of 30min to obtain red mud-based high-iron sulfoaluminate cementitious material clinker. S2. Add 20g of desulfurized gypsum, 35g of Class II fly ash, and 15g of auxiliary modifier to the red mud-based high-iron sulfoaluminate cementitious material clinker obtained in step S1, mix evenly, and grind through a 200-mesh sieve to obtain the red mud-based cementitious material.
[0029] Example 3 A method for preparing a red mud-based cementitious material: Before preparing red mud-based cementitious materials, surface modifiers, modified red mud, and auxiliary modifiers are prepared first: The preparation of surface modifiers includes the following steps: S131. Mix 1.5g KH-550, 0.7g titanate coupling agent NDZ-101, 17g anhydrous ethanol and 2g deionized water, adjust the pH to 4.5 with glacial acetic acid, and hydrolyze with magnetic stirring at 250r / min for 40min. S132. Mix 27g stearic acid, 0.6g hexadecyltrimethylammonium bromide and 600g anhydrous ethanol, and stir at 300r / min in a 70℃ water bath until completely dissolved; S133. Mix the solutions obtained in steps S131 and S132 and stir at 250 r / min for 15 min to finally obtain the surface modifier.
[0030] The preparation of modified red mud includes the following steps: S11. Mix 90g red mud, 8g potassium hydroxide, 1.5g calcium chloride, 0.9g magnesium sulfate, 2.5g desulfurized gypsum, and 13g carbide slag, and mix at a speed of 40r / min for 25min. S12. Add 50g of deionized water to the mixture obtained in step S11, stir into a paste, age at room temperature for 18h, dry in an oven at 105℃, place in a high-temperature furnace, heat to 800℃ at a heating rate of 7℃ / min, keep warm for 40min, and cool to room temperature. S13. The product obtained in step S12 is mixed with 270g of surface modifier and stirred in a water bath at 70℃ for 18h. After filtration, the mixture is washed three times with anhydrous ethanol and dried at 59℃ to constant weight before passing through a 200-mesh sieve to obtain modified red mud.
[0031] The preparation of the auxiliary modifier includes the following steps: S21. Mix 12g of glass powder and 13g of slag powder in a ball mill at a speed of 250r / min for 22min, and then pass the mixture through a 200-mesh sieve to obtain a primary mixed powder. S22. Stir 0.8g of polycarboxylate superplasticizer and 0.4g of naphthalene-based high-efficiency superplasticizer at low speed until they are mixed evenly to obtain a secondary mixed powder; S23. The primary mixed powder, the secondary mixed powder and 0.7g of organosilicon water-repellent agent are mixed in a V-type mixer at 30r / min for 15min to finally obtain the auxiliary modifier.
[0032] The preparation of red mud-based cementitious materials includes the following steps: S1. Mix 20g modified red mud, 40g desulfurized gypsum, 30g aluminum ash, 12g coal gangue and 0.9g borax evenly, and calcine in a high-temperature furnace at a heating rate of 8℃ / min, a calcination temperature of 1120℃ and a holding time of 20min to obtain red mud-based high-iron sulfoaluminate cementitious material clinker. S2. Add 15g of desulfurized gypsum, 30g of Class II fly ash, and 12g of auxiliary modifier to the red mud-based high-iron sulfoaluminate cementitious material clinker obtained in step S1, mix evenly, and grind through a 200-mesh sieve to obtain the red mud-based cementitious material.
[0033] Comparative Example 1 The only difference between Comparative Example 1 and Example 1 is that no auxiliary modifier was added in this comparative example; the other steps are exactly the same in Comparative Example 1 and Example 1.
[0034] Comparative Example 2 The only difference between Comparative Example 2 and Example 1 is that no surface modifier was added in this comparative example; the other steps are exactly the same in Comparative Example 2 and Example 1.
[0035] Comparative Example 3 The only difference between Comparative Example 3 and Example 1 is that the modified red mud in this comparative example is replaced with Bayer process high-sodium red mud. The other steps are exactly the same in Comparative Example 3 and Example 1.
[0036] Performance testing: Appendix Figure 5 A photograph of the red mud-based high-ferric sulfoaluminate cementitious material clinker obtained in Example 1 of this invention; attached. Figure 6 The image shows the XRD pattern of the red mud-based high-ferrous sulfoaluminate cementitious material clinker obtained in Example 1 of this invention. (See attached image.) Figure 5-6 It can be seen that the red mud-based high-ferrous sulfoaluminate cementitious clinker is dark gray to blackish brown, with irregular particle shapes and a rough surface, exhibiting the typical appearance of cement clinker. The uneven particle size distribution and the presence of some sharp-edged particles indicate that partial melting and sintering occurred during the calcination process, resulting in a dense clinker structure.
[0037] Appendix Figure 7 This is a photograph of the finished red mud-based cementitious material obtained in Example 1 of the present invention. As can be seen in the figure, the cementitious material is a uniform light gray to grayish-brown powder with a consistent color and no obvious color spots or foreign matter inclusions. Compared to the dark appearance of calcined clinker, the finished product is slightly lighter in color, which is due to the addition of desulfurized gypsum (light color) and Class II fly ash (light gray) during the compounding stage. The cementitious material particles are fine and well-dispersed, with no visible agglomerates or coarse particle residues.
[0038] The mechanical properties of the red mud-based cementitious materials obtained in Examples 1-3 and Comparative Examples 1-3 were tested according to GB / T 17671 "Test Method for Strength of Cement Mortar (ISO Method)". The mortar mix ratio was set as follows: cement: standard sand: water = 1:3:0.5; specimen size: 40mm × 40mm × 160mm prism; curing conditions: temperature (20±2)℃, relative humidity ≥90%; flexural strength and compressive strength were tested after 28 days.
[0039] The efflorescence resistance of the red mud-based cementitious materials obtained in Examples 1-3 and Comparative Examples 1-3 was tested according to the test method for efflorescence resistance in JC / T 1024 "Wall Finishing Mortar" and GB / T 9263 "Efflorescence Resistance Test Method". The cementitious materials were mixed with water according to standard consistency and molded into specimens of 100mm × 100mm × 50mm, and cured for 28 days. The four sides of the specimens were sealed with epoxy resin or paraffin, leaving only the top and bottom surfaces exposed. The specimens were immersed in distilled water (conductivity <50μS / cm) at (20±2)℃ to a depth of 20mm for 24 hours, then removed and dried in a 60℃ oven to constant weight. This constituted one cycle, and 15 cycles were performed consecutively. After every 5 cycles, the surface efflorescence was photographed and recorded. The percentage of white precipitate coverage was calculated using image analysis to obtain the efflorescence area ratio. Surface precipitates were collected, and the mass of precipitates per unit area was weighed to obtain the efflorescence amount. The efflorescence grade was also assessed: Grade 0 – no efflorescence; Grade 1 – slight, area <10%; Grade 2 – moderate, area 10%-30%; Grade 3 – severe, area 30%-60%; Grade 4 – extremely severe, area >60%. The final results are shown in Table 1 below. Table 1. Performance Test Results As shown in Table 1, the red mud-based cementitious materials obtained in Examples 1-3 outperformed the comparative examples in all aspects. This demonstrates that the synergistic effect of modified red mud, surface modifier, and auxiliary modifier significantly inhibited efflorescence. While achieving a fundamental transformation of the red mud particle surface from hydrophilic to superhydrophobic, it also cuts off the necessary "water-salt" migration chain for efflorescence at its source, endowing the red mud-based cementitious materials with active anti-efflorescence capabilities. This invention is low-cost, uses simple equipment, and is easy to scale up for industrial production. It addresses the engineering challenges of easy efflorescence, whitening, and salt precipitation / pulverization in cementitious materials made from high-sodium red mud, while simultaneously addressing the large-scale disposal of red mud solid waste. Therefore, it has significant market value.
[0040] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a red mud-based cementitious material, characterized in that, The preparation steps include the following: S1. By weight, 15-25 parts modified red mud, 30-50 parts desulfurized gypsum, 20-40 parts aluminum ash, 10-15 parts coal gangue, and 0.5-1.5 parts borax are mixed evenly and calcined in a high-temperature furnace to obtain red mud-based high-iron sulfoaluminate cementitious material clinker. S2. Add 10-20 parts of desulfurized gypsum, 25-35 parts of Class II fly ash, and 10-15 parts of auxiliary modifier to the red mud-based high-iron sulfoaluminate cementitious material clinker obtained in step S1, mix evenly and grind through a 200-mesh sieve to obtain the red mud-based cementitious material. The preparation of the modified red mud includes the following steps: S11. By weight, mix and stir 80-100 parts red mud, 6-10 parts potassium hydroxide, 0.5-2.5 parts calcium chloride, 0.5-1.5 parts magnesium sulfate, 2-3 parts desulfurized gypsum, and 10-16 parts carbide slag for 20-30 minutes. S12. Add 40-60 parts of deionized water to the mixture obtained in step S11, stir into a paste, age at room temperature for 12-24 hours, dry in an oven at 100-110℃, place in a high-temperature furnace, heat to 750-850℃, keep warm for 30-60 minutes, and cool to room temperature. S13. Mix the product obtained in step S12 with 250-300 parts of surface modifier, stir and react in a water bath at 60-80℃ for 12-24 hours, filter and wash 3-4 times, dry at 58-60℃ to constant weight and pass through a 200-mesh sieve to finally obtain modified red mud.
2. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, The preparation of the surface modifier includes the following steps: S131. By mass, mix 1-2 parts KH-550, 0.5-1 parts titanate coupling agent NDZ-101, 15-20 parts anhydrous ethanol and 1-3 parts deionized water, adjust the pH to 4-5 with glacial acetic acid, and hydrolyze with magnetic stirring for 30-60 minutes. S132. Mix 25-30 parts of stearic acid, 0.4-1 parts of hexadecyltrimethylammonium bromide and 500-700 parts of anhydrous ethanol, and stir at 200-400 r / min in a water bath at 60-80℃ until completely dissolved. S133. Mix the solutions obtained in steps S131 and S132 and stir at a speed of 200-300 r / min for 10-20 min to finally obtain the surface modifier.
3. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, The preparation of the auxiliary modifier includes the following steps: S21. By weight, 10-15 parts of glass powder and 10-15 parts of slag powder are dry ball-milled in a ball mill at a speed of 200-300 r / min for 15-30 min, and then passed through a 200-mesh sieve to obtain primary mixed powder. S22. Stir 0.5-1 parts of polycarboxylate superplasticizer and 0.2-0.5 parts of naphthalene-based high-efficiency superplasticizer at low speed until they are evenly mixed to obtain a secondary mixed powder; S23. Mix the primary mixed powder, the secondary mixed powder, and 0.3-1 part of organosilicon water-repellent agent in a V-type mixer at 20-40 r / min for 10-20 min to finally obtain the auxiliary modifier.
4. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, The heating rate during calcination in step S1 is 5-10℃ / min.
5. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, In step S1, the calcination temperature is 1100-1200℃, and the calcination holding time is 10-30 min.
6. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, The stirring speed in step S11 is 30-50 r / min.
7. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, In step S12, the heating rate of the high-temperature furnace is 5-10℃ / min.
8. The method for preparing a red mud-based cementitious material according to claim 1, characterized in that, The cleaning solution used in step S13 is anhydrous ethanol.
9. The method for preparing a red mud-based cementitious material according to claim 2, characterized in that, The stirring speed in step S131 is 200-300 r / min.
10. A red mud-based cementitious material, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.